OPTIMALISASI PROSES EKSTRAKSI MINYAK KAYU PUTIH MELALUI METODE RE-DISTILASI DALAM SKALA LABORATORIUM DAN PILOT PLANT - Rifqi Sufra; Cika Amalia Shabira; Aiman Firjatullah; Misbahudin Alhanif; Yusron Darojat; Desi Riana Saputri; Vina Alfionita; Rizki Sheldian; Tantri Liris Nareswari (Jurnal Inovasi Teknik Kimia, 2025)
Cajuput oil is an essential oil of high economic value and is widely used in the pharmaceutical and health industries. However, national production remains suboptimal, partly due to the low 1,8-cineole content. This study aims to compare improvements in cajuput oil quality achieved through laboratory-scale and pilot-scale redistillation processes. Redistillation was applied to cajuput oil obtained from the initial distillation, using young leaves, mature leaves, and mixed leaves as raw materials. The evaluation included organoleptic characteristics, refractive index, and 1,8-cineole content determined by GC–MS analysis. The results indicate that the highest 1,8-cineole content was achieved by redistilling young leaves, reaching 83.84%, and all distillates complied with the quality standards specified in SNI 3954:2014. The re-distillation process was proven to enhance color clarity, aroma, and chemical quality of cajuput oil. Therefore, redistillation shows strong potential for application at the production scale to support the development of high-quality cajuput oil using green technology.